Documenting a long-term development model in the slums of Delhi. Issue 1 (December 2016) - Morrow, Martha; Armstrong, Greg; Dayal, Prarthna; Kermode, Michelle
Abstract Background Achieving development outcomes requires the inclusion of marginalised populations that have the least opportunity to participate in and benefit from development. Slum dwellers often see little of the 'urban advantage', suffering more from infectious diseases, increasing food costs, poor access to education and health care, inadequate water and sanitation, and informal employment. A recent Cochrane Review of the impact of slum upgrading strategies found a dearth of unbiased studies, making it difficult to draw firm conclusions. The Review calls for greater use of process data, and qualitative alongside quantitative methods of evaluation. India is a lower middle income nation with large gender disparities and around 65 million slum inhabitants. The Asha Community Health and Development Society, a non-governmental organisation based in Delhi, has delivered a multi-sectoral program across 71 slums since 1988. This article reports on a mixed-method study to document measureable health and social impacts, along with Asha's ethos and processes. Methods Several observational visits were made to 12 Asha slums where informal discussions were had with staff and residents (n = 50). Asha data records were analysed for change over time (and differences with greater Delhi) in selected indicators (maternal-child health, education, child sex ratio) using descriptive statistics. 34 semi-structured individual/small group interviews and 14 focus group discussions were held with staff, residents, volunteers, elected officials, civil servants, bankers, diplomats, school principals, slumlords and loan recipients (n = 147). Results Key indicators of health and social equity improved over time and compared favourably with those for greater Delhi. The Asha model emphasises rights, responsibilities, equity and non-violence. It employs strategies characterised by long-term involvement, systematic protocols and monitoring, development of civil society (especially women's and children's groups) to advocate for rights under the law, and links with foreign volunteers and fund-raisers. Stakeholders agreed that changes in community norms and living conditions were at least partly attributable to the Asha model. Conclusions While lacking a control group or complete baseline data, evidence suggested substantial improvements in slum conditions and social equity. The Asha model offers some lessons for slum (and broader) development.